EFFECTIVE USAGE OF DRONES IN INDOOR MANUFACTURING SITES - Veres, Péter; Chuvilina, Olesya; Cservenák, Ákos; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2022)
The usage of drones for transportation, entertainment and media purposes was greatly increased in the last decade. Major and ambitious improvements are being made in this scientific field to reduce the weight of the units, to increase the amount of stored energy relative to the weight, to make more efficient engines, propellers and bodies to increase the flight time. This study approaches the reduction of energy usage from elsewhere: with proper planning of the drones' routes, the energy usage can be decreased. This approach can also be used in industry purposed drones, like the nowadays highlighted indoor drones, whose purpose they are to do simple logistical tasks near manufacturing areas. In this paper these drones will presented with a new energy use model.